Odpowiedzi

2010-03-18T17:00:34+01:00
A) 10= -3x-2x
10= -5|:10
x= -2

Najlepsza Odpowiedź!
2010-03-18T17:02:32+01:00
Rozwiąż równania.
a) -3x=2x-10
-3x-2x=-10
-5=-10/:(-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9/:3
x=3

c) 10=4-2x
2x=-10+4
2x=-6/:2
x=-3

d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/:(-2)
x=-3/2

e) 2(x+1)=1
2x+2=1
2x=-2+1
2x=-1/:2
x=-1/2

f) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7/:(-1)
t=-7

g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=4+6
x=10/:1
x=1

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-2y-y=-18+18
y=0

i) (x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=7+10+3
-5x=20/:(-5)
x=-4
2010-03-18T17:05:00+01:00
A)
-3x=2x-10
-3x-2x = -10
- 5x= -10 / : (-5)
x=2
b)
2x-2=7-x
2x+x = 7+2
3x= 9 / : 3
x= 3
c)
10=4-2x
2x= 4-10
2x= -6 / : 2
x= -3
d)
-(2x-1)=4
-2x+ 1= 4
-2x= 4-1
-2x= 3 / :(- 2)
x= (-1,5)
e)
2(x+1)=1
2x+2 = 1
2x=1-2
2x= -1 / : 2
x= - 0,5
f)
2t-(3t+1)=6
2t-3-1=6
2t=6+3+1
2t=10 / : 2
t= 5
g)
-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
i)
(x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3-10-7
-5x=0 / : ( -5)
x= 0

:)